The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1002/cyto.990060311
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of mouse spermatogenic function following exposure to ethylnitrosourea

Abstract: The effects of the mutagenic agent ethylnitrosourea ( E m on spermatogenic function and sperm chromatin structure were studied by flow cytometry and the results compared with sperm head morphology measurements. Groups of mice received daily exposures ranging from 0 to 75 mgkg body weight x 5 days and were sacrificed 28 days later. Fresh testicular cell suspensions and epididymal sperm were stained with acridine orange (AO) and measured by flow cytometry. Sperm nuclei were isolated, fixed, rehydrated, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
4

Year Published

1986
1986
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(80 citation statements)
references
References 34 publications
1
74
0
4
Order By: Relevance
“…It showed that sperm nuclear DNA was more resistant to heat-induced denaturation in fertile compared with infertile men and bulls (Evenson et al, 1980a). Heat-induced denaturation has since been replaced with acid-induced denaturation due to the similarity of results and the greater ease of the low pH technique (Darzynkiewicz et al, 1975;Evenson et al, 1985). A collaborative study showed that SCSA parameter values of 115 men seeking infertility counseling at the andrology laboratory affiliated with the National Hospital in Oslo, Norway, were twice those of men with proven fertility .…”
Section: Sperm Chromatin Structure Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…It showed that sperm nuclear DNA was more resistant to heat-induced denaturation in fertile compared with infertile men and bulls (Evenson et al, 1980a). Heat-induced denaturation has since been replaced with acid-induced denaturation due to the similarity of results and the greater ease of the low pH technique (Darzynkiewicz et al, 1975;Evenson et al, 1985). A collaborative study showed that SCSA parameter values of 115 men seeking infertility counseling at the andrology laboratory affiliated with the National Hospital in Oslo, Norway, were twice those of men with proven fertility .…”
Section: Sperm Chromatin Structure Assaymentioning
confidence: 99%
“…Much of the development and establishment of the SCSA as a meaningful biological assay for sperm nuclear integrity were conducted on rodent and livestock systems to study toxicology and fertility (Evenson et al, 1985(Evenson et al, , 1989a(Evenson et al, ,b, 1993a(Evenson et al, ,b,c, 1994Ballachey et al, 1987Ballachey et al, , 1988Evenson and Jost, 1993;Sailer et al, 1995a,b;Evenson, 1999a). One study with our laboratory showed that SCSA-defined chromatin damage in bovine spermatozoa negatively affects early embryo formation from what appear to be normally fertilized eggs (Ellington et al, unpublished).…”
Section: Data Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations of chromatin in abnormally shaped spermatozoa have focused on DNA content, chromatin structure or on both (Pinkel et al, 1983;Evenson et al, 1985Evenson et al, , 1986. In most instances, these analyses involved large populations of spermatozoa without regard to their indi¬ vidual shape.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm samples were analyzed by the sperm chromatin structure assay (Darzynkiewicz 1979;Ballachey et al 1987Ballachey et al , 1988. In the sperm chromatin structure assay, sperm are first treated for 30 s at an acid pH (1.2) which induces DNA denaturation in sperm with abnormal chromatin structure (Evenson et al 1985). Cells were then stained with acridine orange which, when intercalated into (1985) reported that implanting bulls with Ralgro@ at 48 d of age resulted in decreased scrotal circumference, but implanting bulls at2l5 d of age had no effect on scrotal circumference.…”
mentioning
confidence: 99%